Vortex nucleation in a Bose–Einstein condensate: from the inside out. (4th November 2016) - Price, R M; Trypogeorgos, D; Campbell, D L; Putra, A; Valdés-Curiel, A; Spielman, I B
Abstract: We observed a new mechanism for vortex nucleation in Bose–Einstein condensates (BECs) subject to synthetic magnetic fields. We made use of a strong synthetic magnetic field initially localized between a pair of merging BECs to rapidly create vortices in the bulk of the merged condensate. Unlike previous implementations and in agreement with our Gross–Pitaevskii equation simulations, our dynamical process rapidly injects vortices into our system's bulk, and with initial number in excess of the system's equilibrium vortex number.